2017
DOI: 10.1002/tal.1443
|View full text |Cite
|
Sign up to set email alerts
|

Reliability analysis of wind turbines under non‐Gaussian wind load

Abstract: Summary Based on translation models, both Gaussian and non‐Gaussian wind fields are generated using the harmony superposition method for examining the reliability of a typical wind turbine at operational and parked conditions. Using the blade aerodynamic model and multibody dynamics, wind turbine responses are calculated and then probability characteristics are analyzed in details. The short‐term extreme response distribution is estimated by the average conditional exceedance rate method at each mean wind spee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Therefore, we should investigate the assumption of the normal distribution of the expected damage based on how the number of required 10-minute realizations for CLT to hold for each load channel in the wind turbine. If the assumption of Gaussian wind and thus Gaussian narrow-band loads does not hold, the results and behaviors will be different (Marques and Benasciutti, 2020, 2021; Shuang and Song, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we should investigate the assumption of the normal distribution of the expected damage based on how the number of required 10-minute realizations for CLT to hold for each load channel in the wind turbine. If the assumption of Gaussian wind and thus Gaussian narrow-band loads does not hold, the results and behaviors will be different (Marques and Benasciutti, 2020, 2021; Shuang and Song, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Do et al [12] estimated fatigue life of wind turbine tower bases throughout Colorado and discussed the effects of wind distribution and turbulence intensity. Shuang and Song [13] investigated crack initiation and growth life of wind turbine blades by using the linear cumulative damage theory and linear crack propagation theory and found that non-Gaussian characteristics of wind inflows had a noticeable influence on both extreme response and fatigue damage. Since it is very difficult to estimate the residual stress distribution along the crack path, as pointed out by Colombi and Doliñski [14], in the previous research, the effect of welding residual stress on the fatigue life of welded joint welds was neglected.…”
Section: Introductionmentioning
confidence: 99%